Modelling of hydrogen diffusion in a steel containing micro-porosity. Application to the permeation experiment. (30th April 2023) - Yaktiti, A.; Dreano, A.; Gass, R.; Yvert, T.; Carton, J.F.; Christien, F.
Abstract: Two numerical models based on non-equilibrium and local equilibrium approaches respectively were developed to simulate hydrogen transport in porous metals, taking account of gaseous hydrogen trapping inside the micro-porosities. They were applied to the case of hydrogen permeation in a cast steel at room temperature. Numerical simulations revealed that the two models are equivalent under certain conditions. A parametric analysis was performed to explore the effect of external hydrogen fugacity, hydrogen solubility and porosity fraction on the hydrogen diffusion behavior. A comparison between experimental permeation data and the numerical results showed reasonable agreement considering no input parameter was adjusted. Graphical abstract: Image 1 Highlights: Hydrogen diffusion in a metal containing micro-porosity is modelled. Trapping of gaseous hydrogen inside the porosity is considered. Two different approaches: non-equilibrium and local equilibrium. Non equilibrium approach based on reaction flux at the metal – porosity interface. Comparison to the permeation experimental data.